Quantitative computer tomography analysis of post-operative subdural fluid volume predicts recurrence of chronic subdural haematoma. (July 2014) - Xu, Fei-Fan; Chen, Jin-Hong; Leung, Gilberto Ka Kit; Hao, Shu-Yu; Xu, Long; Hou, Zong-Gang; Mao, Xiang; Shi, Guang-Zhi; Li, Jing-Sheng; Liu, Bai-Yun
Abstarct Background: Post-operative volume of subdural fluid is considered to correlate with recurrence in chronic subdural haematoma (CSDH). Information on the applications of computer-assisted volumetric analysis in patients with CSDHs is lacking. Objective: To investigate the relationship between haematoma recurrence and longitudinal changes in subdural fluid volume using CT volumetric analysis. Methods: Fifty-four patients harbouring 64 CSDHs were studied prospectively. The association between recurrence rate and CT findings were investigated. Results: Eleven patients (20.4%) experienced post-operative recurrence. Higher pre-operative (over 120 ml) and/or pre-discharge subdural fluid volumes (over 22 ml) were significantly associated with recurrence; the probability of non-recurrence for values below these thresholds were 92.7% and 95.2%, respectively. CSDHs with larger pre-operative (over 15.1 mm) and/or residual (over 11.7 mm) widths also had significantly increased recurrence rates. Bilateral CSDHs were not found to be more likely to recur in this series. On receiver-operating characteristic curve, the areas under curve for the magnitude of changes in subdural fluid volume were greater than a single time-point measure of either width or volume of the subdural fluid cavity. Conclusions: Close imaging follow-up is important for CSDH patients for recurrence prediction. Using quantitative CT volumetric analysis, strong evidence was provided that changes in the residual fluid volume during the 'self-resolution' period can be used as significantly radiological predictors of recurrence.